DYNAMICS of PROTEIN CONTENT in the TISSUES of RAT BRAIN STRUCTURES under DESTRUCTION of the AUDITORY and VESTIBULAR APPARATUS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article considered the identification of the circadian seasonal rhythms and agerelated dynamics of total protein contentin the tissues of rat brain structures during ontogenesis against thedestruction of the auditory and vestibular apparatus. It has beenstated that proteincontent in the tissues of rat brain structures changes significantly.
Keywords: rat, brain, auditory and vestibular apparatus, ontogenesis, protein, circadian and seasonal rhythms.